O elementach wiedzy naukowej w etymologiach ludowych (nienaukowych) nazw polskich miejscowości - Rogowska-Cybulska, Ewa (Slavia Occidentalis, 2019)
The goal of this article is to present the fundamental types of such pseudo-origins. The collated examples of approximately a thousand of association origins of Polish names of locations, excerpted from various printed and online texts, written questionnaires and oral interviews, indicate three types of non-academic origin employing elements of academic knowledge.